2018
DOI: 10.1115/1.4041207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soybean Biodiesel Addition on Tribological Performance of Ultra-Low Sulfur Diesel

Abstract: The purpose of this work was to study the influence of soybean biodiesel addition in ultra-low sulfur diesel (ULSD) on its tribological behavior under low-amplitude reciprocating conditions, simulating the operation of a fuel injector system. The methodology was divided into three parts: the first was the fuel preparation and its physicochemical characterization, where were studied four fuels (diesel, soybean biodiesel, and mixtures of them).The following step was the evaluation of the fuel tribological proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Processes 2021, 9, 272 2 of 15 acid to ultra-low sulfur non-additive 0# diesel as an anti-wear agent, wherein the wear scar diameter and the coefficient of friction were reduced by 60.3% and 95.7%, respectively [6]. Soybean oil and other vegetable oils were researched as raw material to synthesize monoethanolamides as lubricating additives for low-sulfur marine fuel, and the average wear scar diameter (WS 1.4) was less than 520 µm when the concentration of monoethanolamides was 80-140 ppm [7]. Tomic et al conducted research using biodiesel oil obtained from sunflower oil as an additive and added it to low-sulfur diesel oil (fossil diesel oil) with a volume ratio of 3%, finding that the lubrication properties of low-sulfur diesel oil were significantly improved and the wear scar diameter was reduced by 42% [8].…”
Section: Et Al Added the High Oil Fattymentioning
confidence: 99%
“…Processes 2021, 9, 272 2 of 15 acid to ultra-low sulfur non-additive 0# diesel as an anti-wear agent, wherein the wear scar diameter and the coefficient of friction were reduced by 60.3% and 95.7%, respectively [6]. Soybean oil and other vegetable oils were researched as raw material to synthesize monoethanolamides as lubricating additives for low-sulfur marine fuel, and the average wear scar diameter (WS 1.4) was less than 520 µm when the concentration of monoethanolamides was 80-140 ppm [7]. Tomic et al conducted research using biodiesel oil obtained from sunflower oil as an additive and added it to low-sulfur diesel oil (fossil diesel oil) with a volume ratio of 3%, finding that the lubrication properties of low-sulfur diesel oil were significantly improved and the wear scar diameter was reduced by 42% [8].…”
Section: Et Al Added the High Oil Fattymentioning
confidence: 99%
“…As per ASTM D6079-11, measurements were taken for the COF, film %, and WSD. The results demonstrated that increasing the amount of biodiesel enhances film formation and reduces the friction coefficient [107].…”
Section: The Role Of Dieselmentioning
confidence: 94%
“…Transesterification reaction has been carried out using short chain alcohols with lipids in the presence of a acid, alkali, and enzymatic catalysts. The most of the world biodiesel is produced from edible oils such as olive oil, sunflower oil, soybean oil, and palm oil [6][7][8][9]. The edible oilseeds are easily available on large scale.…”
Section: Introductionmentioning
confidence: 99%